Vasoplegia: A Review - Iqbal Ratnani; Rohan Kumar Ochani; Asim Shaikh; Hafsa Nazir Jatoi (Methodist DeBakey Cardiovascular Journal)
Vasoplegia is a condition characterized by persistent low systemic vascular resistance despite a normal or high cardiac index, resulting in profound and uncontrolled vasodilation. Vasoplegia may occur due to various conditions, including cardiac failure, sepsis, and post-cardiac surgery. In the cardiac cohort, multiple risk factors for vasoplegia have been identified. Several factors contribute to the pathophysiology of this condition, and various mechanisms have been proposed, including nitric oxide, adenosine, prostanoids, endothelins, the renin-angiotensin-aldosterone system, and hydrogen sulfide. Early identification and prompt management of vasoplegia is crucial to prevent development of shock. This review expands upon the different vasopressors used in management of vasoplegia, including catecholamines such as norepinephrine, dopamine, epinephrine, phenylephrine, and other agents including vasopressin, methylene blue, angiotensin II, hydroxocobalamin, vitamin C, thiamine, and corticosteroids (ie, hydrocortisone). It also emphasizes the importance of conducting further research and making advancements in treatment regimens for vasoplegia.